Perbandingan Struktur Obyek pada Bahasa Arab dan Bahasa Indonesia - Khoirul Huda (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Objects become one of the discussions in both Indonesian and Arabic grammar which serves to form basic sentences in sentences that are transitive predicated, clarify the meaning of sentences, and form a unity or completeness of mind. Therefore, the author will examine the differences and similarities about objects or maf'ulbih in Arabic and Indonesian so that a learner will easily understand the structure of the sentence in texts with different themes. This research was conducted using a qualitative approach with content analysis method. The research data are in the form of Arabic object structures in the Al-Jazirah Online newspaper and the structure of Indonesian objects in the Tempo kora. The results of this study are the equations of the structure of objects in Arabic and Indonesian, the equations concerning the type of words used, namely both nouns both in Indonesian and Arabic. The differences in the structure of the objects of the two languages ​​can be seen from the order of placement of objects, in Arabic the object may overtake the subject and the predicate does not have to be after the predicate, but in Indonesian it is not like that.